‘It’s Not a Weakness’: Lived Experiences, Support Systems, and Emotional Wellbeing in Caesarean Birth among Postpartum Women in Nigeria. - Michael, Itoro T; Michael, Turnwait O (Student’s Journal of Health Research Africa, 2025)
Background: Caesarean section (CS) is an obstetric intervention for preventing maternal and neonatal complications. Despite its benefits, CS in Nigeria is influenced by cultural beliefs, stigma, and emotional responses, with limited research exploring how these factors affect women’s experiences and mental well-being after surgery. This study examined the lived experiences of postpartum women who delivered by CS in selected Nigerian health facilities, focusing on emotional well-being and support systems. Methods: A qualitative phenomenological design was employed in four Local Government Areas of Ibadan, Oyo State. Data were collected through 11 in-depth interviews and two focus group discussions involving 24 women aged 22–49 years who had undergone CS within the previous five years. Purposive sampling was used to ensure variation in age, education, and residence. Audio-recorded interviews were transcribed and analyzed thematically with ATLAS. Results: Of the 24 participants, thirteen resided in urban areas while eleven resided in rural areas. Five major themes emerged: (1) Pathways to caesarean delivery, highlighting that decisions were largely driven by medical necessity and often involved joint decision-making with spouses; (2) Emotional responses and mental adjustment, ranging from fear and anxiety to calm acceptance influenced by clinical communication and faith; (3) Sociocultural interpretations and stigma, including narratives that associate CS with weakness or spiritual failure; (4) Support systems and recovery experiences, with strong spousal, family, and respectful healthcare support reported as central to recovery; and (5) Future preferences and advice to others, where many participants expressed willingness to undergo CS again, emphasizing the primacy of maternal and child safety. Conclusions: Caesarean birth is more than a clinical procedure; it is a deeply social and emotional experience. Recommendation: Supportive communication from healthcare professionals, family involvement, mental health and counselling, and efforts to dispel negative cultural myths around CS are essential to improving women’s psychosocial outcomes.